Electrically tunable Si-based THz photomodulator using dielectric/polymer surface gating - Romain, X; Wilshaw, PR; Stantchev, RI; Miao, T; Mou, S; Niewelt, T; McNab, S; Pain, SL; Grant, NE; Pickwell-MacPherson, E; Bonilla, RS; Murphy, JD (IEEE, 2024)
Silicon-based terahertz (THz) photomodulators suffer from a modulation speed limited by the lifetime of the charge carriers photoexcited in the silicon. We report a silicon-based THz photomodulator scheme offering real-time reconfiguration of the switching behavior by manipulation of effective charge carrier lifetime. Atomic layer deposition was used to coat silicon samples with dielectric layers to passivate the surfaces with a conductive polymer (PEDOT:PSS) subsequently deposited to enable electrical gating over the whole surface. The resulting gated photomodulators are characterized using photoconductance decay and photoluminescence imaging. A gated photomodulator with HfO2 passivation is then implemented into a THz time domain spectroscopy setup to demonstrate the potential for live photomodulation optimization during a single-pixel imaging experiment. We use the device to achieve a real-time improvement of the signal-to-noise ratio of the images by a factor of 8.